A "Buildup" of Speech Intelligibility in Listeners With Normal Hearing and Hearing Loss. (October 2018) - Best, Virginia; Swaminathan, Jayaganesh; Kopčo, Norbert; Roverud, Elin; Shinn-Cunningham, Barbara
The perception of simple auditory mixtures is known to evolve over time. For instance, a common example of this is the "buildup" of stream segregation that is observed for sequences of tones alternating in pitch. Yet very little is known about how the perception of more complicated auditory scenes, such as multitalker mixtures, changes over time. Previous data are consistent with the idea that the ability to segregate a target talker from competing sounds improves rapidly when stable cues are available, which leads to improvements in speech intelligibility. This study examined the time course of this buildup in listeners with normal and impaired hearing. Five simultaneous sequences of digits, varying in length from three to six digits, were presented from five locations in the horizontal plane. A synchronized visual cue at one location indicated which sequence was the target on each trial. We observed a buildup in digit identification performance, driven primarily by reductions in confusions between the target and the maskers, that occurred over the course of three to four digits. Performance tended to be poorer in listeners with hearing loss; however, there was only weak evidence that the buildup was diminished or slowed in this group.